進行上顎歯肉癌に対する逆行性超選択的動注化学放射線療法 - 光藤, 健司 (日本口腔外科学会雑誌, 2018)
Squamous cell carcinoma (SCC) of the maxillary gingiva is rare and there is only a few reports concerning this cancer. Standard treatment of resectable oral SCC, including carcinoma of the maxillary gingiva, is surgery with or without adjuvant therapy. For patients with locally advanced maxillary gingival SCC, extended resection with reconstructive surgery causes loss of oral function and aesthetic loss. We developed retrograde superselective intra-arterial chemotherapy with radiotherapy for advanced oral cancers to preserve organ. This review was conducted to evaluate the outcome of SCC of the maxillary gingiva and efficacy of retrograde superselective intra-arterial chemoradiotherapy for locally advanced maxillary gingival SCC.